The synthesis of 1,2,4-triazines bearing the residues of higher alcohols in the 5-position via the ipso-substitution of cyano group under the solvent-free conditions - A. P. Krinochkin; D. S. Kopchuk; E. S. Starnovskaya; Ya. K. Shtaiz; A. F. Khasanov; I. S. Kovalev; O. S. Taniya; G. V. Zyryanov; V. L. Rusinov; O. N. Chupakhin (Chimica Techno Acta)
A convenient method for the obtaining of 3,6-diaryl-1,2,4-triazines substituted with  residues of higher alcohols in the position of C5 via the ipso-substitution of cyano group in under the solvent free conditions was reported. This method indicates a new example for the functionalization of the 1,2,4-triazines via the substitution of the cyano group.